Pengaruh Pengendalian Internal Terhadap Pelaporan Keuangan (Survei pada Perusahaan Tekstil Di Kota Bandung) - Yunes Riany; Ferdi Kristian; Rapina Rapina (Jurnal Riset Akuntansi dan Bisnis, 2016)
This study aims to determine and demonstrate empirically the effect of internal control on financial reporting in many textile companies (PT. Mitra Jaya Sakti, PT. Binausaha Cipta Prima and PT. Unggul Bukit Kencana) in Bandung City, and determine the degree of influence. Data used in this research is primary data collected by distributing questionnaires. The respondents were employees in administration and accounting as much as 39 respondents. Data were analyzed using simple regression analysis with SPSS program. Data processing was performed starting from analysis of respondents, validity test, reliability test, classical assumption test, hypothesis testing and coefficient of determination. The results showed that the average ratings of respondents on internal control and financial reporting classified as good categories. Testing of hypothesis proves there is influence between internal control on financial reporting.